2022
DOI: 10.3390/vaccines10071045
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Cytokine Levels, Kidney and Heart Function Biomarkers, and Expression Levels of Angiotensin-Converting Enzyme-2 and Neuropilin-1 in COVID-19 Patients

Abstract: Background: Higher expression of angiotensin-converting enzyme-2 (ACE-2) in addition to neuropilin-1 (NRP-1) can lead to a cytokine storm which is correlated to higher mortality rate and contributes to the progression of renal diseases and the pathogenesis of coronary heart disease (CHD) in COVID-19 patients. Aim: We herein sought to examine correlations between cytokine levels, ACE-2 and NRP-1 expression, renal function biomarkers, and cardiac enzymes in COVID-19 patients. Patients and Methods: For the study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…This study showed that liver function biomarkers were significantly higher in severe patients than in non-severe patients. This was in line with the findings of Henry [41], Sultan et al [42,43], who found that biomarkers of liver and renal function, inflammation, cardiac injury, and coagulation profile were higher in severe and critical patients compared to non-severe patients. According to Wu et al [44], liver injury can be caused by viral infection of bile duct cells or antiviral medication-induced functional impairment.…”
Section: Discussionsupporting
confidence: 91%
“…This study showed that liver function biomarkers were significantly higher in severe patients than in non-severe patients. This was in line with the findings of Henry [41], Sultan et al [42,43], who found that biomarkers of liver and renal function, inflammation, cardiac injury, and coagulation profile were higher in severe and critical patients compared to non-severe patients. According to Wu et al [44], liver injury can be caused by viral infection of bile duct cells or antiviral medication-induced functional impairment.…”
Section: Discussionsupporting
confidence: 91%
“…This study showed that liver function biomarkers were signi cantly higher in severe patients than in non-severe patients. This was in line with the ndings of Henry [41], Sultan et al [42,43], who found that biomarkers of liver and renal function, in ammation, cardiac injury, and coagulation pro le were higher in severe and critical patients compared to non-severe patients. According to Wu et al [44], liver injury can be caused by viral infection of bile duct cells or antiviral medication-induced functional impairment.…”
Section: Discussionsupporting
confidence: 90%
“…These results are in concordance with those of previous publications [ 39 , 40 , 41 , 42 ], which recommended that patients check cardiac markers at admission, which helps medical staff predict the severity of patients in the later stage, and these cardiac biomarkers in serum could act as prognostic biomarkers in COVID-19 patients. As stated by Li et al [ 40 ] and Sultan et al [ 43 ], the mechanisms of actions of COVID-19 to induce heart injury include specific binding to functional receptors on cardiomyocytes and immune-mediated myocardial injury. This postulation was supported by the results of the present study, which revealed a positive significant correlation between serum activity of CK-MB, a potent biomarker of cardiomyocytes’ injury, and ACE2, NRP-1, TLR2, and TLR4 expression levels.…”
Section: Discussionmentioning
confidence: 99%